Efficacy of diffusion-weighted imaging in symptomatic and asymptomatic multiple sclerotic plaques - Farzad Tahmasebi Arashloo; Farnaz Fahimi Hanzaei; Behnaz Sedighi; Ghazaleh Amjad; Ladan Younesi (Journal of Family Medicine and Primary Care, 2019)
Introduction: Magnetic resonance imaging (MRI) currently accompanies clinical findings in disease diagnosis, patients' follow-up, assessment of drugs complications, and evaluation of treatment response. Although contrast-enhanced MRI (CE-MRI) is considered as the imaging modality of choice for multiple sclerosis (MS), due to disease chronicity, applying multiple doses of gadolinium-based contrast agents (GBCAs) increases the risk of nephrogenic syndrome in patients with acute (ARF) and chronic renal syndromes (CRF). Moreover, the effect of gadolinium on the fetus is not well-known in pregnant patients. Therefore, this study evaluates the possibility of replacing postcontrast images with physiologically based MRI sequences such as diffusion weighted imaging (DWI) and apparent diffusion coefficient (ADC). Method: We prospectively evaluated 26 patients with known multiple sclerosis. The patients with MS attacks and the asymptomatic patients who were referred for follow-up were enrolled. Conventional MRI including postcontrast T1W, DWI, and ADC were performed for all patients. The signal intensity (SI) of all enhancing and nonenhancing plaques of more than 10 × 10 mm size were investigated in all sequences and analyzed. Results: A total of 83 plaques were detected in T2-FLAIR sequences of which 51 plaques were enhanced (68%) after gadolinium administration. While 42 MS plaques had hypersignal intensity in DWI (56%), 32 plaques had iso- or hyposignal intensities in DWI (44%). No statistically significant values were obtained. Conclusion: Although DWI could not replace CE-MRI, using these two modalities together could increase detection of active MS plaques and alter patients' therapy and prognosis.